Refleksi Praktek Harmful Traditional Practices di Indonesia - Dwi Astuti; Rosalia Widhiastuti Sri Lestari (LPPM IAIN Parepare, 2020)
Sexual violence against women that occurs in several countries, including Indonesia, is not only a legal phenomenon, but also closely related to tradition, which are greatly influenced with constructions of injustice gender-relations, or called harmful traditional practices. Sexual violence against women based on its tradition often goes unnoticed because it was considered as a common thing, however in fact it was a very detrimental practice to women. This research was conducted using a library research method. The study discribes the solution for the problem of sexual violence against women based on traditional values ​​that underlie harmful traditional practices. This problem can be solved in a various steps, changing substance of the rules in the tradition that rise harmful traditional practices, give awareness about gender-equality, integrating gender-equality in law enforcement agencies and policy makers and empowering women to fight harmful traditional practices.